The Effect of Data-Based Targeting, Service Personalization, and Content Quality on Consumer Loyalty in E-Commerce in Jakarta - Judijanto, Loso; Sopyan, Sopyan; Muhtadi, Muhamad Ammar (Westscience Press, 2025)
This study examines the influence of content quality, data-based targeting, and service personalization on consumer loyalty in Jakarta's e-commerce sector. Using a quantitative approach, data were collected from 150 respondents through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that content quality exerts the strongest influence on consumer loyalty, followed by data-based targeting and service personalization. Content quality enhances customer trust and satisfaction, while data-driven targeting effectively tailors marketing efforts to consumer preferences. Service personalization, though significant, has a smaller impact compared to the other variables. These findings emphasize the importance of integrating content quality, targeting, and personalization strategies to foster loyalty in the competitive e-commerce landscape. The study provides valuable insights for businesses aiming to optimize their marketing strategies and enhance customer retention in Jakarta’s dynamic digital marketplace.